Song Recommendations Based on Artists with Cosine Similarity Algorithms and K-Nearest Neighbor - Budiman, Muhammad Arief; Mastrika Giri, Gst. Ayu Vida (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2020)
The development of the music industry is currently growing rapidly, millions of music works continue to be issued by various music artists. As for the technologies also follows these developments, examples are mobile phones applications that have music subscription services, namely Spotify, Joox, GrooveShark, and others. Application-based services are increasingly in demand by users for streaming music, free or paid. In this paper, a music recommendation system is proposed, which the system itself can recommend songs based on the similarity of the artist that the user likes or has heard. This research uses Collaborative Filtering method with Cosine Similarity and K-Nearest Neighbor algorithm. From this research, a system that can recommend songs based on artists who are related to one another is generated.